Salivary testosterone and cortisol levels in borderline personality disorder before and after a 12-week group dialectical behavior therapy intervention - Dyson, Tori; Thomas, Susan J.; Townsend, Michelle L.; Finch, Adam; South, Alexandra; Barkus, Emma; Walter, Emma; Mendonca, Carley; Grenyer, Brin F. S.; Pickard, Judy A. (Frontiers in Psychology, 2023)
Background Borderline Personality Disorder (BPD) is a chronic, debilitating, and difficult to treat condition. BPD has recently been linked to steroid hormone dysregulation and medical conditions characterized by disturbed androgen metabolism. This study aimed to investigate cortisol and testosterone levels in BPD, and changes in hormones following psychological treatment. Methods Participants with BPD (n = 33) completed a 12-week Dialectical Behavior Therapy group program. Pre and post salivary testosterone and cortisol were analyzed. Baseline hormones in the BPD group were compared to age-and-sex matched controls (n = 33). Non-parametric tests were utilized to investigate group differences, pre-post treatment hormone and symptom changes, and associations between symptoms and hormone levels. Results Participants with BPD had significantly higher testosterone levels than controls. Mean testosterone levels in females with BPD were double that of female controls. Testosterone and cortisol levels were related, and some BPD symptoms were associated with with hormone levels. BPD symptoms reduced significantly with treatment, however pre to post hormone levels did not change. Conclusions This study supports an association between BPD symptoms and neuroendocrine dysfunction at baseline, however we found no reduction in hormone dysfunction post treatment. Further research into relationships between stress signaling and neuroendocrine disturbances in BPD may inform aetiological and treatment models. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12618000477224. Registered on 3 April 2018.